The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1292/jvms.64.699
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Isotonic Sodium Bicarbonate Solution for Alkalizing Effects in Conscious Calves.

Abstract: ABSTRACT. After intravenous (IV) infusion of various volumes of 1.35%-isotonic sodium bicarbonate solution (ISB), acid-base equilibrium, blood pressure, plasma volume and biochemical parameters in healthy Holstein calves were studied. Four calves each were randomly assigned to the low-dose (LD; IV infusion of 5 ml/kg ISB), middle-dose (MD; IV infusion of 10 ml/kg ISB) and the high-dose groups (HD; IV infusion of 15 ml/kg ISB). Administration volumes of ISB in the LD, MD and HD groups were decided based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
21
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…However, clinicians in veterinary practice use various coefficients of bicarbonate distribution when calculating bicarbonate requirements (for example, 0.3 [12], 1/3 [9], 0.5 [1,8], or 0.6 [5,18]). A previous study [16] indicated that the apparent coefficient of distribution of bicarbonate was 0.401 in normal Holstein calves. In this study, therefore, 0.4 was used as the coefficient of distribution.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…However, clinicians in veterinary practice use various coefficients of bicarbonate distribution when calculating bicarbonate requirements (for example, 0.3 [12], 1/3 [9], 0.5 [1,8], or 0.6 [5,18]). A previous study [16] indicated that the apparent coefficient of distribution of bicarbonate was 0.401 in normal Holstein calves. In this study, therefore, 0.4 was used as the coefficient of distribution.…”
mentioning
confidence: 93%
“…A previous study [16] indicated that isotonic sodium bicarbonate solution (ISB, 1.35% NaHCO 3 ) could restore the acid-base equilibrium without altering plasma osmolarity, hemodynamic status and respiratory function in normal Holstein calves. Therefore, ISB in this study we used to restore spontaneous metabolic acidosis in calves, in order to confirm its safety and alkalizing effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…If treatment with oral fluids is unsuccessful, intravenous restoration for the acid-base disorder is performed [6][7][8]. Although lactated Ringer's solution is used to replace the volume of total body water and to correct to electrolyte status in small animals and horses, it dose not usually correct the metabolic acidosis in calves with severe diarrhea [6,11,12,15,16]. Sodium bicarbonate is specifically effective for acute and severe metabolic acidosis because it has rapid effect when given intravenously [7,9,15,16].…”
mentioning
confidence: 99%
“…Although lactated Ringer's solution is used to replace the volume of total body water and to correct to electrolyte status in small animals and horses, it dose not usually correct the metabolic acidosis in calves with severe diarrhea [6,11,12,15,16]. Sodium bicarbonate is specifically effective for acute and severe metabolic acidosis because it has rapid effect when given intravenously [7,9,15,16]. Nevertheless, rapid administration or an overdose of sodium bicarbonate solution has been associated with paradoxical cerebrospinal fulid acidosis, leftward shift of the oxyhemoglobin dissociation curve leading to decreased downloading of oxygen, intracellular shift of potassium in exchange for hydrogen ions causing hypokalemia, tetany due to decreased ionized calcium, and overshot alkalosis [2,5].…”
mentioning
confidence: 99%